2020
DOI: 10.3389/fonc.2020.01126
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of METTL3 Promotes Metastasis of Triple-Negative Breast Cancer by m6A Methylation-Mediated COL3A1 Up-Regulation

Abstract: The abnormal m6A modification caused by m6A modulators is a common feature of various tumors; however, little is known about which m6A modulator plays the most important role in triple-negative breast cancer (TNBC). In this study, when analyzing the influence of m6A modulators ( METTL3, METTL14, WTAP, FTO , and ALKBH5 ) on the prognosis of breast cancer, especially in TNBC using several on-line databases, methyltransferase-like 3 ( METTL3 ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 26 publications
5
98
0
Order By: Relevance
“…(4) The deregulation of m 6 A methylation may be related to the downregulation of ECM in GO specimens. In this study, the increased m 6 A methylation was associated with the downregulation of ECM in the GO specimen, which was consistent with Yu et al's study that showed that increased m 6 A methylation may result in the decreases of the expression of collagen which is a major component of ECM [36]. We found that the significantly enhanced transcript of WTAP (as components of the mammalian m6A methyltransferase complex) was associated with downregulation of ECM genes in GO specimens.…”
Section: Discussionsupporting
confidence: 92%
“…(4) The deregulation of m 6 A methylation may be related to the downregulation of ECM in GO specimens. In this study, the increased m 6 A methylation was associated with the downregulation of ECM in the GO specimen, which was consistent with Yu et al's study that showed that increased m 6 A methylation may result in the decreases of the expression of collagen which is a major component of ECM [36]. We found that the significantly enhanced transcript of WTAP (as components of the mammalian m6A methyltransferase complex) was associated with downregulation of ECM genes in GO specimens.…”
Section: Discussionsupporting
confidence: 92%
“…All the results suggested that METTL3 might increase circMETTL3 expression in an m6A dependent manner. It illustrated METTL3 increased circMeETTL3 expression, derived from its own, to promote breast cancer progression by its methyltransferase activity [24,25]. Another component in m6A methyltransferase enzymes, KIAA1429 and its circKIAA1429 were also highly expressed and promoted hepatocellular carcinoma advancement [26,43], showing the similar mode as METTL3 and circMETTL3 in breast cancer.…”
Section: Circmettl3 Is Upregulated In a M6a-dependent Mannermentioning
confidence: 85%
“…m6A modi cation is a dynamic process, controlled by methyltransferase enzymes (including METTL3, METTL14, WTAP, KIAA1429 et al) and demethylase enzymes (ALKBH5 and FTO) [17]. Previous studies showed these proteins played important roles in breast cancer developments [18][19][20][21][22], especially METTL3, which is the key component in methyltransferase enzymes [20,[23][24][25]. For example, METTL3 could promote breast cancer progression via inhibiting tumor suppressor let-7 g or targeting Bcl-2 [20,25], though another study showed METTL3 inhibited metastasis of triple-negative breast cancer by decreasing COL3A1 [24].…”
mentioning
confidence: 99%
“…Therefore, DEGs were initially screened, and the most valuable top 5 node genes were further mined through the PPI network; these genes were COL3A1, FN1, COL1A2, POSTN and IL-6. The upregulation of COL3A1 is positively related to the methylation of METTL3 in breast cancer [15]. FN1 is related to TNM staging, lymph node metastasis and OS and promotes the metastasis of GC cell lines [12].…”
Section: Discussionmentioning
confidence: 99%